Sub-inhibitory concentrations of oxacillin modulate biogenesis and function of extracellular vesicles secreted by oxacillin-sensitive methicillin-resistant Staphylococcus aureus - Ran, Zhaoxia; Hao, Minghui; Guo, Binxin; Wang, Junrui (Frontiers in Microbiology, 2025)
BackgroundExtracellular vesicles (EVs) derived from Staphylococcus aureus (S. aureus) carry multiple components, such as toxins, antigens, and resistance determinants, whose production is influenced by exposure to β-lactam antibiotics. However, systematic studies on the effects of β-lactam antibiotics on the release and functions of EVs remain limited.MethodsExtracellular vesicles (EVs) were isolated from the OS-MRSA (OS-200) strain by ultracentrifugation, including both EVs untreated with antibiotics and those exposed to sub-inhibitory concentrations of oxacillin (OI-EVs). Proteomic analysis was performed using liquid chromatography-tandem mass spectrometry (LC-MS/MS). The functional changes of these EVs were further assessed through erythrocyte hemolysis assays, biofilm formation assays, measurement of cytokines, and cell invasion assays.ResultsExposure to sub-inhibitory concentrations of oxacillin (half and one-eighth of the minimum inhibitory concentration [MIC]) significantly enhanced the secretion of OI-EVs and increased the abundance of several proteins, including penicillin-binding protein 2, EmrB, Hlg, and enolase, in a concentration-dependent manner. Notably, EV1/2MIC exhibited more pronounced functional changes and enhanced hemolytic activity against rabbit red blood cells. Also, EV1/2MIC exhibited significant promoting effects on biofilm formation of OS-200. Additionally, OI-EVs stimulated the secretion of interleukin-6 and tumor necrosis factor-α by THP-1 macrophages in a dose-dependent manner and demonstrated greater penetration potential into A549 lung epithelial cells.ConclusionExposure to sub-inhibitory concentrations of oxacillin significantly altered the secretion and composition of EVs, highlighting a novel relationship between antimicrobial exposure, exosome biogenesis, and OS-MRSA pathogenicity. These findings provide new insights into how β-lactam antibiotics influence host–pathogen interactions by modulating the secretion of bacterial vesicles.